Pengaruh Keong Mas (Pomacea canaliculata) Sebagai MOL dan Lama Perendaman Terhadap Pertumbuhan Mucuna bracteata - Obet Edom Ginting; Bayu Pratomo; Sari Anggraini; Edy Fachrial; Aisar Novita (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Ginting OE, Pratomo B, Anggraini S, Fachrial E, Novita A. 2020. Effect of golden snail (Pomacea canaliculata) as MOL and soaking time on the growth of mucuna bracteata. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Golden snail (Pomacea canaliculata) is a pest on rice plants. Golden snails (Pomacea canaliculata) contain minerals that can be used as nutrients for plants so that they can be used as MOL (local microorganisms). The purpose of this study was to determine the effect of giving MOL snails and the duration of immersion on the growth of Mucuna bracteata. This study used a factorial randomized block design experimental method with 2 replications. The first factor was the concentration of MOL snails (K) with 4 levels of treatment, namely K0 (0%), K1 (15%), K2 (30%), K3 (45%) while the second factor was immersion time (M) with 4 levels of treatment M0 (0 minutes), M1 (15 minutes), M2 (30 minutes), M3 (45 minutes). The results showed that the interaction between the concentration of MOL snails (Pomacea canaliculata) and the immersion time did not have a significant effect on all parameters. Various concentrations of MOL snail (Pomacea canaliculata) and immersion time did not significantly affect the growth of Mucuna bracteata.